A Facile Route for Synthesis of (±)-Dinoprost, (±)-Carboprost and Its Analogs - Shankar, M.; Rama Mohan, H.; Viplava Prasad, U.; Hari Krishna, M.; Mareswar Rao, P.; Lakshmikumar, T.; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2012)
A general synthetic approach was developed for (±)-dinoprost (1), (±)-carboprost (2) and their analogs (3-5) through a key intermediate (6). Compound 6 can be converted into the target compounds in two or three steps. Diastereomeric separation was accomplished easily for obtaining (±) dinoprost. Separation of diastereomers was difficult for (±) carboprost and their analogs. Key intermediate 6 was obtained, in turn, from (±)-corey lactone.